Ejercicios Hipopresivos en la fuerza del Core en adultos - Guaman Choca, Henry Fabricio (2024)
The research entitled “Hypopressive Exercises on Core Strength in Adults” aims to evaluate the influence of hypopressive exercises on Core Strength Training in adults. The project was developed through a bibliographic analytical typology using data published in scientific sources such as books, scientific articles and reports. The investigative work has a type of technical - methodological research, a quasi-experimental research design, a quantitative approach, that is, data were gathered pre and post application of the Core Test - (Evaluation of abdominal stabilizing strength) in the administrative staff of the National University of Chimborazo (La Dolorosa Campus). A 10-week intervention was carried out with 3 training sessions per week, the objective of each training session was to improve abdominal strength and improve the quality of life of the subjects participating in the study, because the administrative staff remains seated in front of a computer because it is part of their job, they do not do any type of physical activity during their work day, which causes the loss of abdominal strength and reduces the waist circumference. Finally, it is proven that the hypopressive exercise program has a positive impact as long as it is worked correctly, continuously and with dedication. In addition, a very important external factor that intervenes within this program is that they have a balanced diet, exercises Hypopressive exercises are the best way to work on abdominal strength and at the same time reduce the waist circumference. They are easy exercises that take little time to perform and with this it is proposed that more people put into practice hypopressive exercises, since that provide many health benefits.